2020
DOI: 10.1038/s41598-020-59641-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of VKORC1 and CYP2C9 on acenocoumarol dose, stroke recurrence and intracranial haemorrhage in Spain

Abstract: fàbregas 9 , Luis prats-Sánchez 9 , pol camps-Renom 9 , francisco purroy 10 , Serafi cambray 11 , María del Mar freijo 12 , cristòfol Vives-Bauzá 13 , Silvia tur 14 , Maria-Àngels font 15 , elena López-cancio 16,17 , Acenocoumarol is an oral anticoagulant with significant interindividual dose variations. Variants in CYP2C9 and VKORC1 have been associated with acenocoumarol maintenance dose. We analysed whether any of the 49 polymorphisms in CYP2C9 and VKORC1 previously associated with acenocoumarol maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Paré et al investigated whether some genetic component accounted for the concentration of the active dabigatran metabolite and whether these genes were also implicated in the efficacy and safety of the drug using GWAS [ 137 ]. Polymorphisms in CES1 were associated with trough and peak metabolite concentration, while ABCB1 was found to be associated with peak concentration only.…”
Section: Stroke Pharmacogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paré et al investigated whether some genetic component accounted for the concentration of the active dabigatran metabolite and whether these genes were also implicated in the efficacy and safety of the drug using GWAS [ 137 ]. Polymorphisms in CES1 were associated with trough and peak metabolite concentration, while ABCB1 was found to be associated with peak concentration only.…”
Section: Stroke Pharmacogenomicsmentioning
confidence: 99%
“…Polymorphisms in CES1 were associated with trough and peak metabolite concentration, while ABCB1 was found to be associated with peak concentration only. ABCB1 is important for the entry of dabigatran-etexilate (prodrug form) into the blood and CES1 metabolizes dabigatran-etexilate to dabigatran to activate the drug [ 137 ]. In this GWAS, the CES1 polymorphism, which is associated with a 15% reduction in the trough metabolite concentration, was also linked with a decrease in any bleeding risk.…”
Section: Stroke Pharmacogenomicsmentioning
confidence: 99%
“…Actually, evidence has emerged that several genetic variants modulate certain pharmacological drugs which prevent stroke, such as antiplatelet agents and anticoagulants. Cullell et al (2020) found that several variants in CYP2C9 (encoding cytochrome P450 2C9) and VKORC1 (encoding vitamin K epoxide reductase complex subunit 1) associated with acenocoumarol (an oral anticoagulant) maintenance dose were also associated with ICH risk. Moreover, Falcone et al (2014) demonstrated that APOE ε2 and APOE ε4 were associated with warfarin related LICH ( Falcone et al, 2014 ).…”
Section: Future Directions In Ich Geneticsmentioning
confidence: 99%
“… 8 Additionally, there is evidence that polymorphisms in the CYP2CP gene are associated with stroke occurrence and recurrence in Spanish and Chinese populations. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%